Türkiye'de Sanayi Sektörü - Iktisadi Büyüme Ilişkisinin Kaldor Hipotezi Çerçevesinde Test Edilmesi - Ibrahim Arisoy (Turkish Economic Association, 2008)
– This study first provides an outline of Kaldor's growth model and then tests its relevance to the economic experience of Turkey during the period 1963-2005 by using cointegration and causality tests. Kaldor's first law states that manufacturing is the engine of economic growth, whereas the second proposition, also known as Verdoorn's law, asserts that there is a strong positive casual relationship between manufacturing productivity growth and output growth, due to static and dynamic increasing returns to scale. Kaldor's third law purports that overall growth is positively correlated to employment growth in manufacturing output, and negatively correlated to employment in non-manufacturing sectors. The empirical results, regardless of the specification and estimation techniques employed, suggest that the models can partly explain the developments in the economy to a certain degree.
Keywords: O41; O11; R11; 330; Kaldors Law; Industrial Output; Employment; Productivity; Growth; Wachstumstheorie; Wirtschaftswachstum; Beschäftigung; Produktivität; Schätzung; Türkei